Field collection,preservation and large scale DNA extraction procedures for cassava (Manihot esculenta Crantz.) - Bhattacharjee, Ranjana; Ferguson, Morag E.; Gedil, Melaku A; Dumet, D.; Ingelbrecht, I.L. (2009)
Some genetic studies using molecular methods such as diversity assessment or marker-assisted selection require collection of a large number of samples from fields located in the vicinity or in remote areas, followed by isolation of good quality DNA in a short time span. In the present study, different tissue preservation methods were compared for subsequent DNA extraction using a modified CTAB method in two 96-well plates, following grinding of leaf tissues with a GenoGrinder 2000. We found that preservation of leaf tissues in NaCl-CTAB-azide buffer (as described in Rogstad, 1992) at 4°C is a better storage procedure than preservation at -20°C to obtain good quality DNA. Comparison of DNA extraction with or without use of phenol revealed that the quality of DNA was not drastically affected when non-phenol extraction protocol was used and did not affect PCR amplification. Thus, the recommended DNA extraction procedure allowed us to process 192 samples per day at a cost of $0.80 per sample, with an average yield of 1.8 g, suitable for both PCR and genotyping.